Characterisation of nano-scale precipitates in BOR60 irradiated T91 steel using atom probe tomography - Yeli, G; Strutt, VCI; Auger, MA; Bagot, PAJ; Moody, MP (Elsevier, 2020)
Atom probe tomography has characterised the microstructural changes in T91 steel after BOR60 reactor irradiation at five temperatures between 376 °C and 524 °C to doses between 14.6 dpa and 35.1 dpa. Irradiation-induced precipitation and segregation to carbide/matrix interface induced by neutron irradiation has been characterised. Atom probe tomography characterisation shows that Mn, Ni, Si -rich (MNS-rich) clusters form in T91 steel irradiated in BOR60 reactor at temperatures between 376 °C and 415 °C, which is not observed at higher temperatures 460 °C and 524 °C. The number density, volume fraction and composition of MNS-rich clusters have been characterised. Ni, Mn, Si and P is found to segregate at carbide matrix interface after irradiation at lower temperature and only P segregation is observed at 524 °C.